Case Report: Is Surgical Treatment Beneficial for Intracranial Basal Ganglia Cunninghamellamycosis Following Haematopoietic Stem Cell Transplantation? - Xi, Bixin; Liu, Aiguo; Zhao, Xin; Zhang, Yicheng; Wang, Na (Frontiers in Pediatrics, 2022)
Cunninghamellamycosis is an unusual but often highly fatal mucormycosis caused by Cunninghamella bertholletiae, which belongs to the basal lineage order Mucorales. It is especially fatal when the central nervous system is involved. So far, there are few reported cases of surgical treatment for intracranial mucormycosis in children after allogeneic haematopoietic stem cell transplantation (HSCT). The surgical management of deep-seated basal ganglia fungal lesions remains controversial, and its clinical benefits are not yet well established. Herein, we present a rare case of disseminated mucormycosis caused by C. bertholletiae involving the lung and intracranial basal ganglia after homologous leucocytic antigen-matched sibling donor HSCT. The patient was successfully treated for intracranial cunninghamellamycosis with neuroendoscopic surgery and systemic wide-spectrum antifungal treatment and achieved pulmonary recovery without recurrent C. bertholletiae infection or neurologic sequelae. Over the follow-up period of 13 months, there were no adverse events associated with the intracranial surgical debridement, and the patient remained in good health.